Analysis of the Cellular Response to Different Dental Implant Surfaces: An In vitro Study - Mohammed G. Sghaireen; Mohammad Raji Alrwuili; Nasser Attallah Alenzi; Mohammed Ahmed Aljabab; Rakhi Issrani; Mohammad Khursheed Alam (Wolters Kluwer Medknow Publications, 2024)
Background: Dental implant surfaces play a crucial role in determining the success of osseointegration and long-term stability. Understanding the cellular response to various implant surfaces is essential for optimizing implant design and clinical outcomes. Materials and Methods: In this in vitro study, we investigated the cellular response to different dental implant surfaces. Titanium implants with three distinct surface treatments (polished, acid-etched, and sandblasted) were prepared. Human osteoblast-like cells were cultured on these surfaces, and cellular behaviors including adhesion, proliferation, and morphology were evaluated using standard assays and imaging techniques. Results: Our results revealed significant differences in cellular responses among the different implant surfaces. Cells exhibited higher adhesion and proliferation rates on the acid-etched and sandblasted surfaces compared to the polished surface. Furthermore, cells displayed a more spread-out morphology with well-defined filopodia and lamellipodia on the acid-etched and sandblasted surfaces, indicating enhanced cellular interaction and spreading. Conclusion: The cellular response to dental implant surfaces varies depending on surface characteristics. Acid-etched and sandblasted surfaces promote better cellular adhesion, proliferation, and spreading compared to polished surfaces. These findings underscore the importance of surface modifications in enhancing osseointegration and ultimately improving the success rates of dental implant procedures.